Kirurško zdravljenje zapletov divertikuloze debelega črevesa - Norčič, Gregor (Endoskopska revija, 2009)
Strategy of surgical treatment of diverticular disease has changed over recentyears. In order to confirm the value of a more modern therapeutic approach to the disease, we rewieved the available literature and analysed 101patients operated on for complicated diverticular disease at the Departmentof Abdominal Surgery, University Medical Centre Ljubljana, from the beginning of 2006 to November 2009. There were 45 (44.6 %) emergency operations and 56 (55.4 %) elective procedures. Postoperative mortality in theemergency group was 28.9 %; none of the patients operated on electively died. High mortality rates in patients operated on on an emergency basis is attributable to comorbidities; the influence of surgical technique on the outcome is not yet clear. The optimal timing for elective surgery has not yetbeen determined, but laparoscopic-assisted resection has proved to be the most appropriate surgical technique for diverticular disease.
Keywords: Diverticulosis, Colonic; Urgentna stanja; Complications; Gastrointestinalna krvavitev; Divertikulitis debelega črevesa; Surgery; Retrospektivne študije; Emergencies; Diverticulitis, Colonic; Zdravljenje, izid; Gastrointestinal Hemorrhage; debelo črevo; Peritonitis; therapy; zdravljenje; Treatment Outcome; kirurško zdravljenje; Retrospective Studies